Removal of a congenital corneal dermoid through tumor excision and lamellar keratoplasty in a young child: A case report. Issue 49 (10th December 2021) - Cui, Yanyan; Yin, Shan; Yin, Xuewei; Liu, Yonghui; Zhao, Bojun
Abstract: Rationale: Corneal dermoids are a rare cause of corneal opacification, consisting of abnormal mesoblastic tissue surrounded by epithelium. Here, we describe the case of a 1-year-old child who had a congenital corneal dermoid in the left eye since birth; thus, the patient underwent tumor excision followed by keratoplasty. Patient concern: A 1-year-old girl was brought to the hospital by her parents, who had been noticing a mass on the surface of her left eyeball since birth. The patient had no other previous or concurrent disease nor family history for dermoids. Clinical findings: No abnormalities were present in the cornea and the anterior and posterior segments of the right eye. Eye movement, intraocular pressure, and the position of the upper eyelid of the left eye were normal. No signs of conjunctival hyperemia were present. The tumor presented as a yellowish-pink mass with hair and veins on the surface. Diagnose: The patient was initially diagnosed with a keratoconjunctival tumor of the left eye by a clinical doctor. Interventions: Corneal tumor resection combined with keratoplasty was performed in the patient. Eye drops with 1% cyclosporine were administered 3 times per day to prevent immune rejection. Outcomes: Based on postoperative pathological examinations, the final diagnosis was a corneal dermoid. The patient had an uneventful healing process and rapid corneal re-epithelization. The ocular surface was stable during the follow-up visits, and no complications emerged. Lessons: We report a rare case of congenital corneal dermoid. We learned that close follow-up is needed after surgery in such cases.